ASSESSMENT THE PROPORTION OF RISK FACTORS FOR COMPLICATED SUPRAVESICAL OBSTRUCTIONIN PREGNANCY USING STATISTICAL METHODS (RETROSPECTIVE STUDY) - Mukhtarov, Sh.T.; Khasanov, M.M; Abdufattaev, U.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To assess the proportion of risk factors for the occurrence of complicated supravesical obstruction in pregnant women using statistical methods. Materials and methods: In a retrospective study, data from 361 case histories were analyzed, each of which indicated values for the maximum diameter of the renal pelvis (MADP), data for urinalysis and blood tests, as well as for complicated supravesical obstruction. Results: The difference in the incidence of cases of complicated supravesical obstruction in the risk group and in comparison group is statistically significant, therefore, it can be argued that the MADP value above 22 mm affects to frequency of complicated supravesical obstruction in the population (p<0,001), the same statement is true for urine analysis parameters: WBC (p<0,05) and bacteruria (p<0,05), blood tests: leukocytosis (p<0,01), an increase in leukocyte intoxication index (p<0,01), levels higher than normal values of urea (p<0,05) and creatinine (p<0,05) in blood serum. Conclusion: The increased values of MADP, leukocyturia, bacteruria, blood leukocytosis, as well as urea and creatinine levels are statistically significant risk factors that have a high proportion in the likelihood ratio of developing a complicated course of supravesical obstruction in pregnant women